Systems Analisys Of National Employment From The Technological Aspect And Working Mechanisms - Martono, Aris (Rekayasa Teknologi, 2011)
National employment systems currently lack the optimal data fromthe input data nakertrans service districts / cities have been cut off due tostructural relations official with the center after implementation of regionalautonomy laws since 1999. Besides the force personnel in each unit district/ city level of skill and expertise less understood areas of employment forpersonnel and units of work is a fusion of the department of labor office, theoffice of the department of resettlement,social services and education services. The stakeholders involved on the mechanisms of national employmentsystems also vary depending upon the region. Region I, job seekers andusers of workforce capable of using the internet as a means to earn ayellow card for the job seekers and Obligation Report sent to the officesnakertrans Jobs district / city for the users of labor. Region II, as theinternet inaccessible areas but the population is able to use scanners. Jobdata sent by fax to the offices nakertrans district / city. Job seekers canregister directly to the tribal district offices to get a yellow card. Region IIIexplained that this region does not reach the Internet and its inhabitantsare not able to use the scanner then the mechanism of the Employmentsystem as region II. Building a new organizational structure in the nationalemployment system so that new bodies are performing theirduties and functions it could achieve the expected goals. Build a network of internet and intranet technology to record the new jobseekers and sends vacancies available quickly and easily.